Development of IoT-based Monitoring of the Lithium-Ion Battery Pack for a Two-Wheeled Vehicle Ecosystem - Sonki Prasetya; Muhammad Todaro; Hasvienda M Ridlwan (MBI, 2026)
Electric bicycles with two wheels are increasingly popular as a convenient mode of short-distance transportation. To enhance mobility and promote the use of eco-friendly energy around campus areas, conventional bicycles can be transformed into electric ones using a conversion kit. The main challenge lies in creating a design that is easy to install (plug-and-play) and compatible with various bicycle models. Moreover, monitorized battery condition is an advantage to inform the user. A key advantage of this concept is the inclusion of a universal battery pack equipped with an IoT-based monitoring system. This study aims to design an IOT based battery pack conversion kit powered by a 576 Wh of LiFePO₄ lithium-ion battery type. Experiment results indicate that battery pack of 50 cm × 16 cm × 14 cm dimension with the total weight of 4.5 kg can perform as the energy storage for a converted two-wheeled electric vehicle. The test achieves the speed of 500rpm with 1A current.